Kemukjizatan Ilmiah Pada Kisah Nabi Nuh As, Fir’aun & Keberadaan Manusia Di Bumi Sebelum Adam - Wasalmi Wasalmi (Jurnal Budi Pekerti Agama Islam, 2023)
The Prophets brought evidence in the form of miracles before their people as a challenge they had never faced before. Some Prophets even brought more than one piece of evidence to ensure that they were truly messengers of Allah. This research aims to find out what scientific aspects are contained in the stories of the Prophet Nuh as., Pharaoh and also humans who inhabited the Earth before Adam as.